ENHANCING NATURAL SCIENCE EDUCATION AND DEVELOPING A SYSTEM OF SCIENTIFIC KNOWLEDGE IN ELEMENTARY SCHOOLS - Махмудова Диёра Акмалевна (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This scientific article aims to explore the significance of incorporating natural science education in elementary schools and the methods that can be employed to develop a comprehensive system of scientific knowledge among young learners. It emphasizes the importance of fostering a strong foundation in scientific thinking and the acquisition of fundamental scientific principles during the early stages of education. This paper also discusses the pedagogical approaches and strategies that can be employed for effective natural science instruction in elementary schools.